Status of serum anti-mullerian hormone and lipid profile in polycystic ovarian syndrome: a cross-sectional study at tertiary care centre of central India - Paneri, Sangita; Suslade, Shakti; Bafna, Angurbala; Shreedhar, Jayshee; Sarkar, P. Dey; Verma, Meena (International Journal of Research in Medical Sciences, 2018)
Background: Polycystic ovarian syndrome (PCOS) is the most common cause of chronic anovulation in young women and affects 5 to 10 % of the female population. Anti-Mullerian Hormone (AMH) level indicate the quantity of the ovarian follicle pool and may be a useful marker of ovarian reserves. In order to establish the pattern of change in serum AMH level and its contribution in alteration of lipid metabolism and PCOS related complications the present study was planned. Methods: Study was carried out in M.G.M. medical college, Govt Holker College and K. R. G’s Blessed mom centre from June -2016 to December -2017. The study population consisted total 50 women subjects among them 25 women suffering from PCOS aged between 18 to 35-year taken as case group and 25 age matched healthy women taken as control group. Fasting blood sample was collected from each subject and analyzed for AMH level and Lipid profile level. Results: Results revealed that significantly increased serum AMH, cholesterol, triglycerides, LDL, VLDL levels and significantly decreased HDL levels were observed in PCOS cases when compare to control subjects. Conclusions: Study concluded elevated AMH level leads to increase risk of polycystic ovarian syndrome and PCOS associated hyperlipidemia and other complications.